Etymologisk information i enspråkiga allmänordböcker - Svensén, Bo (Nordiske Studier i Leksikografi, 1997)
Most monolingual general dictionaries can be described as basically synchronic, but some of them also include a diachronic component providing etymological information. This contribution focuses on some structural aspects of the presentation of etymological information in monolingual dictionaries, applying the conceptual and terminological framework used in Nordisk leksikograjisk ordbok [Nordic Lexicographic Dictionary].